If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 89 + -7x = 20x + 17 Reorder the terms: 89 + -7x = 17 + 20x Solving 89 + -7x = 17 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 89 + -7x + -20x = 17 + 20x + -20x Combine like terms: -7x + -20x = -27x 89 + -27x = 17 + 20x + -20x Combine like terms: 20x + -20x = 0 89 + -27x = 17 + 0 89 + -27x = 17 Add '-89' to each side of the equation. 89 + -89 + -27x = 17 + -89 Combine like terms: 89 + -89 = 0 0 + -27x = 17 + -89 -27x = 17 + -89 Combine like terms: 17 + -89 = -72 -27x = -72 Divide each side by '-27'. x = 2.666666667 Simplifying x = 2.666666667
| 2+ln(x)=0/7 | | x^2+15x+12=0 | | 9-9x=194-4x | | C=10t+15 | | 2z=z-6 | | 1=cos(7.75x-120) | | 3/4-a=-3/4 | | (x^2+11x+17)/(x+3) | | 4r-4/r=8/7 | | X+5x=204 | | v^2+24-15=0 | | 3xy-4x+6x-xy+5y= | | 27/10=40/x | | 5x-9=29-5x | | 2x-20+9+3x=180 | | 10/27=x/40 | | 3=e^20x | | -260/-45 | | x^6y^12/x^3y^6 | | 10-10x+20=10-6x | | 6(x+10)(x-8)=0 | | 7x-2y=-10 | | 7t+1/5=t+6/10+t-4/10 | | (5x-8)/(x+6) | | -6x+4=-3x+16 | | 113-4x=14x+15 | | -343=-7(1+6x) | | 7d+(5-8)d+11d= | | 4(6-3x)=36 | | 2x^2+3=9 | | 80-4x=14-8x | | -9t-9=9 |